Utilization of machine learning to improve usability of the feedback process on student learning evaluation results - Agus Hermanto; Mochamad Sidqon; Nurul Fadilah (Jurnal Sistem Informasi, 2021)
This research aims to design an E-learning system with machine learning implementation to assist the process of evaluating student learning outcomes for improving the learning process. The method used is the Cosine Similarity Matching which is a method to measure the comparability between documents or text. In this study, there were 15 students and 15 teachers who were used as samples in the implementation of E-Learning system and evaluation of the usability of E-Learning system using the SUS method. The system testing carried out obtained a fairly good performance, namely the precision test results had a performance of 86.67% and based on the usability test results obtained a value of 61.33 which was counted in the Marginal High category. Thus the E-Learning system that has been built can help facilitate the process of evaluating student learning. It is hoped that this implementation can help make online learning easier.Keywords: Autocorrection Essay, Cosine Similarity, E-Learning, Information System, Machine Learning